Az első világháború a térben - Nagy, Miklós Mihály (Közép-Európai Közlemények, 2014)
Hungarian historical geography has so far paid little attention to the geographical phenomena and processes of World War I. While a great number of academic publications were written between 1914 and 1918 on this matter as well as on the Treaty of Trianon, which was such a shock to Hungarian society, a comprehensive geographical analysis of this world conflict has been missing from the academic literature. The main thesis of the contemporary literature was provided by Arthur Dix in the Geographische Zeitschrift in 1917. This thesis suggests that the European theatre of war in World War I was located ran along the line stretching between Bagdad and Hamburg, and the main geographical features of the world war can be described by the events occurring to the east and west of this line. Dix’s thesis was soon adopted by the academic literature – primarily German – of political geography and geopolitics. Since World War I was primarily a European armed conflict, and the main theaters of operation remained within the boundaries of this continent, the Dix-thesis was appropriate to provide a comprehensive approach to the analysis of military events. At the same time, the German author’s study is an organic part of the processes of scientific history, which indicated an increased interest in military issues by civilian geographers both in Hungary and abroad during World War I. This increased interest renewed the discipline of military geography, the common ground between military science and geography. The present study provides an overview of the author’s geographical research on World War I by expanding on the Dix-thesis by the spatial development of the world war, and its diminishing in Central-Europe and Asia Minor.